Investigation of Hepatitis A and E Viruses in Mussels Collected from the Bosphorus, in Istanbul, Turkey - Short Communication - Yilmaz, Huseyin; Cizmecigil, Utku; Tarakci, Eda Altan; Aydin, Ozge; Yilmaz, Aysun; Calicioglu, Mehmet; Turan, Nuri (Czech Academy Agricultural Sciences, 2018)
Hepatitis A and E viruses (HAV and HEV) are recognised as food-and water-borne infections and shellfish are a well-documented source of these viruses. The presence of HAV and HEV in mussels has not previously been investigated in Bosphorus, Istanbul, Turkey, and therefore the aim of this study was to investigate the frequency of HAV and HEV in mussels collected from this location. A total of 92 pooled samples representing 736 mussels originating along the Bosphorus coast were collected from fish distributors. RNA was extracted using the RNeasy Plant Mini Kit and a TaqMan real-time RT-PCR was performed using primers specific to HAV and HEV. Amongst the 92 pooled samples tested, three (3.3%) were found to be positive for HAV by the TaqMan real-time RT-PCR. No HEV was detected in any of the mussels tested. A 174 bp product was observed on gel electrophoresis with HAV positive samples detected by SYBR Green real-time PCR after reverse transcription. This product was sequenced and confirmed to contain HAV sequences by alignment using the data in GenBank. This is the first report describing the presence of HAV in mussels harvested in the Bosphorus, Istanbul, Turkey, indicating the potential contamination of aquatic environment and risk to public health.
Keywords: hepatitis; mussels; Turkey; virus; real-time RT-PCR